Embryo and Its Mitochondria - Pascale May-Panloup; Magalie Boguenet; Hady El Hachem; Pierre-Emmanuel Bouet; Pascal Reynier (MDPI AG, 2021)
The mitochondria, present in almost all eukaryotic cells, produce energy but also contribute to many other essential cellular functions. One of the unique characteristics of the mitochondria is that they have their own genome, which is only maternally transmitted via highly specific mechanisms that occur during gametogenesis and embryogenesis. The mature oocyte has the highest mitochondrial DNA copy number of any cell. This high mitochondrial mass is directly correlated to the capacity of the oocyte to support the early stages of embryo development in many species. Indeed, the subtle energetic and metabolic modifications that are necessary for each of the key steps of early embryonic development rely heavily on the oocyte's mitochondrial load and activity. For example, epigenetic reprogramming depends on the metabolic cofactors produced by the mitochondrial metabolism, and the reactive oxygen species derived from the mitochondrial respiratory chain are essential for the regulation of cell signaling in the embryo. All these elements have also led scientists to consider the mitochondria as a potential biomarker of oocyte competence and embryo viability, as well as a key target for future potential therapies. However, more studies are needed to confirm these findings. This review article summarizes the past two decades of research that have led to the current understanding of mitochondrial functions in reproduction